PENGARUH SELF HELP GROUP UNTUK MENINGKATKAN KUALITAS HIDUP KELUARGA DALAM MERAWAT PASIEN SKIZOFRENIA - Rizka Yunita; Iin Aini Isnawati; Widya Addiarto (Sekolah Tinggi Ilmu Kesehatan Kepanjen, 2020)
Abstract: Schizophrenia is a mental disorder that requires treatment for a long time. This disease is easy to recur when the individual is under psychological pressure. This condition makes the family as the patient's closest party required to always accompany and assist him in carrying out activities. This situation makes the family feel that they are not free to work so that it makes them feel physically, psychologically and socially depressed as a result, the quality of family life decreases. The purpose of this study was to analyze Self Help Group (SHG) in improving the quality of family life caring for schizophrenia patients. This study used a quasy experimental design with a pre-post test with control group design. The study population was 40 respondents. The sampling technique used purposive sampling which a research sample of 36 respondents divided into 18 respondents in each control and treatment group. The results of this study showed that the average score of family quality of life in caring for schizophrenia patients in the control group before the health education intervention was 88.5 and after intervention was 92.78, while before the intervention in the treatment group was 87.28 and after it was 111.06. The result have significant ρ-value of 0,000 was also obtained, which means that there are differences in the quality of family life in caring for schizophrenic patients after being given intervention in the control and treatment groups. So it can be concluded that SHG is one of therapy applied as an intervention for families in order to improve their quality of life while caring for schizophrenia patients. Keywords: schizophrenia, family, quality of life, self-help group